PERKEMBANGAN PENGUNGKAPAN AKUNTANSI STUDI KASUS KREDIT YANG DIBERIKAN - Herry Hutabarat (Jurnal Akuntansi Bisnis, 2017)
Disclosures as part of the accounting process is continued to develope.. Disclosure of forward looking information, segment disclosures, social responsibility disclosues and social disclosures for nondomesticfinancial statement users is increasing to respond globalization and innovation of financial transaction and the needs of duch information from analyst and investor. Meanwhile to protect the shareholders, investors and others stockholder, the authority (Bank Indonesia and Bapepam),  and accounting institutoin such as Ikatan Akuntan Indonesia (IAI), internacional Accounting Standard (IAS)  are continuing to improve the regulatory disclosure requirements especially din banking industry. These regulations can be read in PAPI (Princip Akuntansi Perbankan Indonesi), Pernyataan Standar Akuntansi Keuangan (PSAK), Internacional Financial Reporting Standards (IFRS).   Due to such development and to get some comparative the writer is tried to make a brief analysis based on library research and PT Bank Mandiri Tbk, annual report 2005 to 2007.     Keywords : Disclosures, PAPI, PSAK, IFRS, Banking Industry